ANALISIS TINGKAT PENDAPATAN USAHATANI BAWANG MERAH DI KECAMATAN SABU BARAT KABUPATEN SABU RAIJUA - Tersiana Tudu; Paulus Un; Alfetri N. P. Lango (Buletin Ilmiah Impas, 2022)
This research has been carried out in West Sabu District, Sabu Raijua Regency with the objectives: 1) To know the Management of Shallot Farming in West Sabu District, Sabu Raijua Regency. 2) To find out the level of shallot Farming income in West Sabu District, Sabu Raijua Regency. 3) To determine the feasibility of onion farming in West Sabu District, Sabu Raijua Regency. In this research used survey method. The number of respondents was 39 people, each with 18 people from the Farmers Group (Mira Ie) of Raemude Village and 21 people from the Farmers' Group (Muri Mada) of Nadawawi Village. The results showed that farming management had been implemented well with the level of onion farming income in the two villages amounting to IDR 1,234,961,250 with an average income of IDR 31,665,673 respondents. The results also show that shallot farming is feasible because it has an R/C Ratio of 4.4. Break Event Point (BEP) analysis results show Production BEP of 2,453.87; and BEP Price of Rp.48,929,687.50.Based on the results of the research, it is expected that farmers to increase the production of shallots should expand their agricultural land so that production results can increase and the amount of income also increases.